1988
DOI: 10.1116/1.584069
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin polymer films for microlithography

Abstract: Unclassified 22a. NAME OF RESPONSIBLE INDIVIDUAL 22b. TELEPHONE (include Area Code) 22c. OFFICE SYMBOL Dr. Kenneth J. Wynne (202) 696-4410 DO FORM 1473,84MAR 83 APR edtion may be used until exhausted. SFUIr" CLASSIFICATION OF THr!

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…1 with surface pressure-area ( -A) isotherms. The -A isotherms are qual-itatively consistent with the previous results [1], [2], [4]. The surface potentials of the sand a-PMMAs increase rapidly from zero even in the region where D 0.…”
Section: Surface Pressure and Surface Potential Of The Floating supporting
confidence: 90%
“…1 with surface pressure-area ( -A) isotherms. The -A isotherms are qual-itatively consistent with the previous results [1], [2], [4]. The surface potentials of the sand a-PMMAs increase rapidly from zero even in the region where D 0.…”
Section: Surface Pressure and Surface Potential Of The Floating supporting
confidence: 90%
“…4,5 Because the LB technique can overcome the weakness of spin-coat films in which molecules are distributed randomly, recently the polymer LB films have been investigated for the application to high-resolution lithographic resists with electron beams or X-ray beams to expose the resist layers deposited on substrates and then with a development process to remove the exposed portions (positive type) or the unexposed portions (negative type) selectively. [6][7][8][9] Previously, we have succeeded in the preparation of fairly uniform polymer LB films using acrylamide polymers having long alkyl chains. 10 Furthermore, we also succeeded in producing the fine patterns by the polymerization of alkylacrylamide monomer LB films 11,12 and the cross-linking reaction in polymer LB films 13 with UV irradiation and electron beams.…”
Section: Introductionmentioning
confidence: 99%
“…The Langmuir−Blodgett (LB) technique has been approved as an effective way to form a defect-free and molecularly ordered ultrathin film with controlled thickness and orientation. , Because the LB technique can overcome the weakness of spin-coat films in which molecules are distributed randomly, recently the polymer LB films have been investigated for the application to high-resolution lithographic resists with electron beams or X-ray beams to expose the resist layers deposited on substrates and then with a development process to remove the exposed portions (positive type) or the unexposed portions (negative type) selectively. …”
Section: Introductionmentioning
confidence: 99%
“…If these become the technologies of choice for manufacturing future IC generations, the high optical absorption in organic materials at these wavelengths would necessitate thin layer imaging ͑TLI͒ techniques, with imaging layer thickness of less than 2000 Å. [4][5][6][7] In this article we report results from a study carried out in a production environment to explore the manufacturability of TLI. 3 A number of studies have shown increases in defect density with reduced resist film thickness in the regime of 30-500 nm.…”
Section: Introductionmentioning
confidence: 99%